Parental Role, Social Media, Peer Support, and Their Associations on Attitude Toward Reproductive Health in Female Students in Junior High Schools, Manokwari, West Papua - Priscilla Jessica Pihahey; Merlin Soripet (Journal of Health Promotion and Behavior, 2023)
Background: The risky behavior of adolescents in Indonesia towards their reproductive health makes adolescents vulnerable to experiencing pregnancy at an early age, pregnancy outside of marriage, unwanted pregnancy, and infection with sexually transmitted diseases to unsafe abortions. Adolescent attitudes toward risky behavior depend on information obtained from parents, peers and social media. This study aimed to determine how much influence the role of parents, social media, and peers had on the attitudes of young women to maintain their reproductive health.Subjects and Method: The research design was an observational analytic research study, with a cross-sectional approach. It was carried out at SMP Negeri 1 and SMP Negeri 2, Manokwari, West Papua in April to July 2022. A total of 130 girls were selected by random sampling. The dependent variable is attitude. The independent variables are the role of parents, peers, and social media. Data analysis with logistic regression model using the STATA 17 program.Results: Parental role (OR= 17.40; 95% CI= 5.32 to 56.90; p <0.001), peers OR= 11.28; 95% CI 3.23 to 39.33; p <0.001), and social media (OR= 7.30; 95% CI= 2.25 to 23.71; p= 0.001) positively and significantly affected positive attitude of reproductive health.Conclusion: The role of parents, peers, and social media influences the positive attitudes of adolescents about their reproductive health.Keywords: reproductive health, attitude, parental role, peers, social media, adolescent.Correspondence:Priscilla Jessica Pihahey. School of Health Polytechnic, Ministry of Health Sorong. Jl. Basuki Rahmat, Klawalu, East Sorong, Sorong 98416, West Papua. Email: pihaheypriscilla@gmail.com. Mobile: +628114852336.Journal of Health Promotion and Behavior (2023), 08(01): 34-43DOI: https://doi.org/10.26911/thejhpb.2023.08.01.05